2014
DOI: 10.1038/nsmb.2890
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering global SUMOylation signaling networks in a site-specific manner

Abstract: SUMOylation is a reversible post-translational modification essential for genome stability. Using high-resolution mass spectrometry, we have studied global SUMOylation in human cells and in a site-specific manner, identifying a total of over 4,300 SUMOylation sites in over 1,600 proteins. Moreover, for the first time in excess of 1,000 SUMOylation sites were identified under standard growth conditions. SUMOylation dynamics were quantitatively studied in response to SUMO protease inhibition, proteasome inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
511
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(560 citation statements)
references
References 53 publications
29
511
2
1
Order By: Relevance
“…SUMOylation of CDK6 during mitosis has been described to block ubiquitylation and subsequent degradation of the enzyme, ensuring its presence during G1/S transition [53]. Additional CDKs and cyclins have been identified as SUMO targets in recent proteomic screens and targeted approaches, including CDK1, CDK9, CDK11 and Cyclin-E, further highlighting crosstalk between SUMOylation and phosphorylation during cell cycle regulation [23,48,54] (Figure 2). …”
Section: Sumoylation and Cyclin-dependent Kinases In Concertmentioning
confidence: 99%
See 2 more Smart Citations
“…SUMOylation of CDK6 during mitosis has been described to block ubiquitylation and subsequent degradation of the enzyme, ensuring its presence during G1/S transition [53]. Additional CDKs and cyclins have been identified as SUMO targets in recent proteomic screens and targeted approaches, including CDK1, CDK9, CDK11 and Cyclin-E, further highlighting crosstalk between SUMOylation and phosphorylation during cell cycle regulation [23,48,54] (Figure 2). …”
Section: Sumoylation and Cyclin-dependent Kinases In Concertmentioning
confidence: 99%
“…Amplification of c-Myc is one of the most frequent events in a wide variety of different cancer types [70]. Recently, c-Myc was found as a SUMO target specifically after heat shock and inhibition of the proteasome, suggesting that SUMOmodified c-Myc is rapidly degraded by the proteasome [48,71,72] (Figure 4). Alternatively, c-Myc is specifically SUMOylated in response to protein-stress as a signalling mechanism.…”
Section: Sumoylation-mediated Regulation Of Oncogenes and Tumor Supprmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several of these proteins have been shown to be SUMOylated on multiple sites, including megakaryoblastic leukemia (translocation) 1 (MKL1) (14), CREB-binding protein (CBP) (15), and PEA3/ETV4 (16). Furthermore, two recent proteomic studies emphasize the potential for more widespread multi-SUMOylation as they found that a large proportion of all SUMO2-modified proteins contain two or more modified lysine residues, with one study reporting that over one-half of the proteins fell into this category, with proteins like ZNF451 having 40 such sites (17,18). In principle, multi-SUMOylation could provide a platform for recruiting proteins containing multiple SIMs as has already been observed for poly-SUMOylation in the form of linear chains.…”
mentioning
confidence: 99%
“…Thus, we subjected the 130 KI‐enriched candidates to network analysis, using the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) at a high confidence (Table S2, Figure S4a). Forty‐two percent of the identified proteins (55 of 130) appeared to be interconnected with an average local clustering coefficient of 0.346, indicating potential identification of secondary interaction‐dependent non‐SUMOylated proteins and confirming that SUMOylation occurs on highly interconnected networks (Figure S4a; Hendriks et al., 2014). Subsequent analysis of the molecular interaction networks with Cytoscape revealed two main core clusters with scores between 9 and 6, with one of the cluster containing proteins of the SUMOylation machinery (Figure S4b).…”
Section: Resultsmentioning
confidence: 99%